2016
DOI: 10.1007/s10900-015-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Communication Barriers and Self-Rated Health in Older Chinese American Immigrants

Abstract: Older Chinese immigrants are a growing population in the United States who experience multiple healthcare communication barriers such as limited English proficiency and low health literacy. Each of these obstacles has been associated with poor health outcomes but less is known about their effects in combination. This study examined the association between healthcare communication barriers and self-rated health among older Chinese immigrants. Cross-sectional survey data were obtained from 705 Chinese American i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…Health literacy can be conceptualised as the social and communication skills as well as the broader health system and community factors required to obtain and use information to promote health and well‐being. Inadequate health literacy is prevalent in Chinese Americans, particularly those with low English proficiency, while Tsoh et al reported that despite having a Chinese speaking primary doctor, most older Chinese American migrants had inadequate health literacy. Similarly, an Australian survey found that compared to English‐speaking participants, those with low English proficiency reported significantly more difficulties with understanding health information, engaging with health care providers, and navigating the health care systems .…”
Section: Introductionmentioning
confidence: 99%
“…Health literacy can be conceptualised as the social and communication skills as well as the broader health system and community factors required to obtain and use information to promote health and well‐being. Inadequate health literacy is prevalent in Chinese Americans, particularly those with low English proficiency, while Tsoh et al reported that despite having a Chinese speaking primary doctor, most older Chinese American migrants had inadequate health literacy. Similarly, an Australian survey found that compared to English‐speaking participants, those with low English proficiency reported significantly more difficulties with understanding health information, engaging with health care providers, and navigating the health care systems .…”
Section: Introductionmentioning
confidence: 99%
“…[34567] For cancer patients with limited English proficiency (LEP), communication can be the main barrier to health care because accessibility to health care is determined by the ability of the patient to interact with the health-care system on various occasions, rather than the accessibility to health care due to insurance status. [89] The complexity of the health-care system, varying expectations for cancer care and provider–patient relationships, and lack of knowledge and support resources can all impede daily management of care. [210] For patients who are unfamiliar with the health-care system, these tasks and processes can be daunting.…”
Section: Introductionmentioning
confidence: 99%
“…International studies also raised concerns over older Chinese immigrants’ lack of help‐seeking attitudes and behaviours and has identified poor health literacy in older Asian immigrant communities, particularly for South Asian and Vietnamese populations in the United Kingdom, United States and Canada, showing difficulty understanding and communicating about cancer screening practices . Levels of health literacy have also been found to be positively correlated with self‐rated health when studied in US‐based older Chinese immigrants . International research recommends the development of interventions to enhance older Asian immigrants’ health literacy and knowledge of health services.…”
Section: Discussionmentioning
confidence: 99%
“…International research recommends the development of interventions to enhance older Asian immigrants’ health literacy and knowledge of health services. Of critical importance was promoting the use of preventative services and addressing stigma surrounding mental illness …”
Section: Discussionmentioning
confidence: 99%